Essence of Managerial Process in Pedagogical Creative Work of V.O.Sukhomlyns’kyi - Viktor Bereka (Pedagogical Discourse, 2011)
Topical problems of educational institution management, defined by V.O.Sukhomlyns’kyi are revealed in the article